THE ARCTIC ENERGY BASKET: TREASURE CHEST OR PANDORA’S BOX? - I. Smagina (BRICS Law Journal, 2016)
The never-ending race after the world’s limited energy resources puts forward a wide range of questions and concerns to be responded to in a short period of time. Even with the boom in renewable sources of energy1 and the provocative forecasts of the collapse of the oil and gas markets2 new opportunities for oil and gas exploration and exploitation are still the focus of global attention. However, what appears new and promising may be deceptive. The abundant yet hard to obtain Arctic oil and gas reserves are an apt illustration of the case. The main question in this regard is whether the Arctic is a treasure chest whose opening will free vast energy resources for future generations or a Pandora’s Box whose opening will let loose irreversible troubles upon humankind.